login
A113885
Recursive sequence with a(n)=a(a(a(n-2)))+a(n-a(n-1)) and a(0)=a(1)=1.
0
1, 1, 2, 2, 4, 3, 6, 3, 9, 3, 5, 8, 6, 6, 15, 7, 6, 10, 15, 7, 9, 8, 17, 9, 12, 8, 21, 9, 16, 8, 23, 12, 12, 14, 15, 16, 12, 14, 18, 15, 15, 24, 18, 14, 30, 14, 21, 28, 18, 18, 19
OFFSET
0,3
FORMULA
a(n) = a(a(a(n-2))) + a(n-a(n-1)) a(0) = a(1) = 1
EXAMPLE
a(5)=3 because a(a(a(5-2)))+a(5-a(5-1)) = ... = 3
MATHEMATICA
a[n_] := a[n] = a[a[a[n - 2]]] + a[n - a[n - 1]] a[0] = a[1] = 1; Table[a[n], {n, 100}]
CROSSREFS
Sequence in context: A140357 A352622 A089265 * A113886 A334952 A220096
KEYWORD
easy,nonn
AUTHOR
Josh Locker (joshlocker(AT)gmail.com), Jan 28 2006
STATUS
approved